Исследование форм днищ для автоматизации проектирования инструмента трения - Середа, В. Г.; Горбач, Е. В.; Паламарчук, В. А. (НТУ "ХПИ", 2012)
Рассмотрены виды днищ, получаемые методом тангенциальной обкатки, и способы их получения. С помощью метода морфологического анализа проведена классификация выпуклых днищ. На её основе выявлены особенности проектирования инструмента трения для обкатки выпуклых днищ. Предложены способы проектирования инструмента в среде DELCAM PowerShape.

The types of the bottoms received by a method of a tangential rolling, and methods of their receiving are considered. By means of a method of the morphological analysis classification of the convex bottoms is carried out. On its basis features of design of the tool of friction for a running in of the convex bottoms are revealed. Methods of design of the tool in the environment of DELCAM PowerShape are offered.
Keywords: тангенциальная обкатка; морфологический анализ; обкатка; DELCAM PowerShape; tangential rolling; bottom; morphological analysis; tool design